Extra uterine growth restriction and its related factors in extremely and very low birth weight babies including 1500 grams admitted to Jammhoria hospital in Benghazi. - I.Kadwar , Aziza; I. Shreef , khadiga; A. Alsaeiti, Isaaida; AM. Aldarogi, Nadia (Benghazi University Medical Journal, 2025)
Abstract Background:Extra-uterine growth restriction (EUGR) in premature infants remains a major challenge for neonatologists worldwide. In the neonatal intensive care unit (NICU), suboptimal nutrition and the fear of advancing feeds are key contributors. Updated feeding protocols that support rapid but safe feeding advancement, breast milk fortification, and close monitoring of growth parameters are essential to achieving optimal nutritional outcomes and preventing long-term neurodevelopmental impairment. Objective: To determine the frequency of extra-uterine growth restriction (EUGR) among premature infants in Benghazi and identify associated risk factors. Method: This cross-sectional study was conducted in Benghazi. Medical records of 107 premature infants were obtained from the neonatal clinic. All preterm infants born at <34 weeks’ gestation and weighing ≤1500 grams were included. Growth measurements at birth, discharge, and 40 weeks corrected age were plotted on Fenton growth charts. Weight <10th percentile was classified as EUGR. A p-value <0.05 was considered statistically significant. Results: EUGR was identified in 85 infants (79%) at discharge and in 63 infants (58.8%) at 40 weeks corrected age. Significant risk factors for EUGR at discharge and at 40 weeks included lower birth weight (p = 0.01; p = 0.005), longer hospital stay (p = 0.007; p = 0.01), small for gestational age (SGA) (p = 0.000; p = 0.02), and sepsis (p = 0.03; p = 0.001). Additionally, gestational age 33–34 weeks (p = 0.001) and multiple births (p = 0.03) were significant risk factors for EUGR at discharge only. Conclusion: Extra-uterine growth restriction is highly prevalent among Libyan premature infants. Lower birth weight, prolonged hospitalization, SGA status, gestational age of 33–34 weeks, and multiple births were significant associated risk factors. Recommendations: Implementation of updated feeding protocols for premature infants in Libya—including rapid but safe advancement of enteral feeds, breast milk fortification, and close monitoring of growth parameters—is essential to improving nutritional outcomes and reducing the risk of EUGR.